Struktur Representasi Pengetahuan Matematis Mahasiswa pada Mata Kuliah Kalkulus Ditinjau Berdasarkan Extended Level Triad ++ - Diah Selviani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to determine the structure of the representation of students' mathematical knowledge in calculus courses based on the Extended Level Triad++. This research is a qualitative research, in the first semester there were 30 students at Dehasen University Bengkulu, the data were obtained by observation, interviews, giving test questions and triangulation, the next step was to do data analysis, make data recapitulation and conclude, and report. Based on the results of the research and discussion, an overview of the structure of the representation of students' mathematical knowledge is obtained, namely: at Pre-Level 0 (Pre-Intra), there are only 2 students; Intra Level (Level 0) there are 5 students; Semi Intra Level (Level 1) there are 5 students; Inter level (Level 2) there are 6 students; Semi Trans Level (Level 3) there are 6 students; Trans Level (Level 4) there are 4 students; and for Trans Level Extended (Level 5) there are 2 students. It is important to know the level of representation of students' mathematical knowledge in calculus courses based on the Extended Level Triad ++. Keywords: Extended Level Triad++, Concept of Function, Representational Structure, Mathematical Knowledge,